PEMETAAN KEBUTUHAN PENDIDIKAN MASYARAKAT PEDESAAN UNTUK PERENCANAAN PROGRAM PEMBERDAYAAN BERBASIS LOGICAL FRAMEWORK STUDI KASUS KECAMATAN SILUQ NGURAI, KUTAI BARAT - Hendra Santoso; Roni Marudut Situmorang (Social Welfare Study Program, 2025)
Abstract. This study aims to identify the current state of education and formulate prioritized educational development needs in four villages within the Siluq Ngurai District—namely Sangsang, Kaliq, Tanah Mea, and Tebisaq. The ultimate goal is to design a sustainable community empowerment program using the Logical Framework Analysis (LFA) approach. A qualitative descriptive methodology was employed, incorporating participatory surveys, field observations, and focus group discussions involving local leaders and key stakeholders. The collected data were categorized based on the ISCED and analyzed to develop tailored educational intervention plans for each village. Findings reveal that the main challenges in educational development include limited access to secondary and higher education, inadequate primary school infrastructure, and a lack of incentives for educators. Tanah Mea and Tebisaq demonstrated the highest levels of educational need, particularly in physical infrastructure and institutional management, while Sangsang and Kaliq emphasized scholarship support and educational transportation. The LFA process produced strategic program designs such as scholarship provision, skills training, transportation support, school renovation, and institutional capacity-building at the village level. To ensure program effectiveness, collaborative efforts between local governments, communities, and educational institutions are essential. This includes the allocation of targeted funding, strengthened leadership roles in educational advocacy, and the development of locally responsive scholarship schemes. Keyword: Rural Education, Logical Framework, Community Empowerment, Educational Needs. Abstrak. Penelitian ini bertujuan untuk mengidentifikasi kondisi pendidikan serta merumuskan kebutuhan prioritas pembangunan pendidikan di empat kampung dalam wilayah Distrik Siluq Ngurai, yaitu Kampung Sangsang, Kaliq, Tanah Mea, dan Tebisaq. Tujuan akhir dari penelitian ini adalah menyusun perencanaan program pemberdayaan masyarakat yang berkelanjutan dengan pendekatan Logical Framework Analysis (LFA). Metode yang digunakan adalah pendekatan deskriptif kualitatif melalui survei partisipatif, observasi lapangan, dan diskusi kelompok terarah yang melibatkan tokoh masyarakat serta pemangku kepentingan lokal. Data yang diperoleh diklasifikasikan berdasarkan kerangka ISCED dan dianalisis untuk merumuskan rancangan program intervensi pendidikan sesuai kebutuhan spesifik tiap kampung. Hasil penelitian menunjukkan bahwa tantangan utama dalam pembangunan pendidikan di wilayah ini meliputi rendahnya akses terhadap pendidikan menengah dan tinggi, buruknya infrastruktur sekolah dasar, serta minimnya insentif bagi tenaga pengajar. Kampung Tanah Mea dan Tebisaq menunjukkan tingkat kebutuhan tertinggi, khususnya dalam aspek fisik dan manajerial pendidikan, sedangkan Kampung Sangsang dan Kaliq lebih fokus pada dukungan beasiswa dan transportasi pendidikan. Penyusunan LFA menghasilkan rancangan program strategis seperti pemberian beasiswa, pelatihan keterampilan, penyediaan sarana transportasi, renovasi sekolah, serta penguatan kapasitas kelembagaan pendidikan di tingkat kampung. Untuk mendukung efektivitas pelaksanaan program, diperlukan sinergi antara pemerintah daerah, masyarakat, dan lembaga pendidikan, termasuk pengalokasian dana khusus untuk pendidikan kampung, peningkatan peran kepala kampung dalam advokasi pendidikan, serta pengembangan program beasiswa berbasis kebutuhan lokal. Keyword: Pendidikan Pedesaan, Logical Framework, Pemberdayaan; Kebutuhan Pendidikan.